EFFECTIVENESS OF THE IMPLEMENTATION OF EUROPEAN AUTONOMOUS AGREEMENT ON MINIMUM REQUIREMENTS IN STANDARD PLAYER CONTRACTS - Augutavičiūtė, Agnė (Teisė, 2016)
The article analyses the effectiveness of the implementation process of the autonomous Agreement on minimum requirements in standard player contracts concluded within the European social dialogue committee for European professional football. Firstly, the article briefly explores pros and cons of the autonomous European social dialogue, then examines the importance of Article 5 of the Agreement in the European professional football regulation and investigates the effectiveness of the implementation process of Article 5 of the Agreement in Poland, Croatia, Slovenia and Lithuania.